The Role of Formative Feedback in Curriculum Materials: Improving Learning Outcomes Through Continuous Assessment - Vrisantya Ika Putri; Yesi Cahya Palupi; Yuli Alfi Laili; Dian Arief Pradana (JOURNAL OF TECHNOLOGY, EDUCATION & TEACHING (J-TECH), 2024)
In education, formative feedback is essential for developing an effective curriculum. This formative feedback can help teachers evaluate progress in understanding the material that has been given and can adjust learning methods to suit students' needs. This way students can see what they are doing well and know what needs to be improved, thus increasing their confidence and motivating them to learn. This research uses qualitative methods to understand how formative feedback is applied in the learning process. The results show that it can improve academic achievement and help students develop critical thinking skills. In addition, formative feedback, which serves as an assessment tool, also serves to create a collaborative and responsive learning atmosphere. Thus, formative feedback in the curriculum is essential to achieve learning outcomes and create better learning experiences for all students.